2006
DOI: 10.1111/j.1472-4669.2006.00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of microbial communities in fault‐bordered aquifers in the Miocene formation of northernmost Japan

Abstract: We investigated the diversity and distribution of archaeal and bacterial 16S rRNA gene sequences in deep aquifers of mid-to late Miocene hard shale located in the northernmost region of the Japanese archipelago. A major fault in the north-west-south-east (NW-SE) direction runs across the studied area. We collected three groundwater samples from boreholes on the south-west (SW) side of the fault at depths of 296, 374 and 625 m below ground level (m.b.g.l.) and one sample from the north-east (NE) side of the fau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 45 publications
2
40
0
1
Order By: Relevance
“…For example, Basso and colleagues (2009) showed that the microbial community of a deep subsurface gas storage aquifer was primarily composed of Firmicutes and δ-Proteobacteria. Other studies reported that the microbial community in groundwater collected in Japan at a depth of 900 m was composed of 40 % Firmicutes and 27 % δ-Proteobacteria (Shimizu et al, 2007), in the same range as the deep aquifer in a Miocene formation (Shimizu et al, 2006). In addition to the possible contribution by Proteobacteria and Firmicutes, we used more specific probes that targeted phylogenetic groups of the SRB within the δ-subclass of Proteobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Basso and colleagues (2009) showed that the microbial community of a deep subsurface gas storage aquifer was primarily composed of Firmicutes and δ-Proteobacteria. Other studies reported that the microbial community in groundwater collected in Japan at a depth of 900 m was composed of 40 % Firmicutes and 27 % δ-Proteobacteria (Shimizu et al, 2007), in the same range as the deep aquifer in a Miocene formation (Shimizu et al, 2006). In addition to the possible contribution by Proteobacteria and Firmicutes, we used more specific probes that targeted phylogenetic groups of the SRB within the δ-subclass of Proteobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, surveys of 16S rRNA genes in environmental DNA have found sequences with 98 to 99% sequence similarity (Fig. 3) in clone YWA05, from a coal seam aquifer located 843 to 907 mbls in northern Japan (48), clone HDBW-WA06, from a fault-bordered aquifer located 374 mbls in the Miocene formation of northern Japan (49), and clones PL-10A1 and 10A6, from production waters of a low-temperature biodegraded oil reservoir in Canada (14). The phylotypes with high sequence similarity within the clade of Methanolobus chelungpuianus and M. psychrophilus may be widespread in terrestrial sediment and the subsurface.…”
Section: Fig 3 Phylogenetic Analysis Of 16s Rrna Genes Showed the Rmentioning
confidence: 99%
“…Investigations of microbial communities have used 16S rRNA gene sequence analysis to characterize archaea in the deep subsurface such as in terrestrial rocks (45,52), petroleum reservoirs (8,9,18,39,40,42,58), faults (37,49,57), coal seams (11,48), gas fields (36), and subseafloor gas hydrates (17,33,35). These studies have demonstrated the abundance and diversity of methanoarchaea.…”
mentioning
confidence: 99%
“…The amplified PCR product was sequenced as previously described (Shimizu et al, 2006), using the following sequencing primers: A25F (as above), U533F (59-GTG-CCAGCMGCCGCGGTAA-39, where M5A or C; Dojka et al, 1998), 0922F (59-GAAACTTAAAKGAATTG-39, where K5G or T; Achenbach & Woese, 1995), 1100F (59-GGCAACGAGCGMGACCC-39; Lane, 1991), U1492R (as above), 1098Ra (59-GGGTCTCGCTCGTTSCC-39, where S5C or G; Mikucki et al, 2003), U907R (59-CCGTCA-ATTCCTTTRAGTTT-39; Dojka et al, 1998), 536-519r (59-GWATTACCGCGGCKGCTG-39, where W5A or T; Lane et al, 1985), 368-353r (59-AGKTTTCGCGCCTGCT-39; Kotelnikova et al, 1998) and 0112aR (59-CCACGTG-TTACTSAGC-39; Achenbach & Woese, 1995 T was most similar (99.9 %) to that of uncultured clone HDBW-WA05 (accession no. AB237738), which had previously been obtained from deep subsurface groundwater of the Wakkanai Formation in the Horonobe area (Shimizu et al, 2006). Phylogenetic trees reconstructed using the neighbour-joining, maximum-parsimony and minimum evolution methods showed that strain HB-1 T clustered with members of the genus Methanosarcina and was most closely related to M. mazei S-6 T and M. frisia C16 T ( Fig.…”
mentioning
confidence: 99%